2010
DOI: 10.1016/j.febslet.2010.07.043
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of Bifidobacterium Longum phosphoketolase; key enzyme for glucose metabolism in Bifidobacterium

Abstract: Edited by Judit OvádiKeywords: Phosphoketolase Thiamine diphosphate Bifidobacterium longum a b s t r a c tThe crystal structure of Bifidobacterium longum phosphoketolase, a thiamine diphosphate (TPP) dependent enzyme, has been determined at 2.2 Å resolution. The enzyme is a dimer with the active sites located at the interface between the two identical subunits with molecular mass of 92.5 kDa. The bound TPP is almost completely shielded from solvent except for the catalytically important C2-carbon of the thiazo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 30 publications
2
33
0
Order By: Relevance
“…Therefore, the product E4P is formed by the interaction of TPP and F6P in the absence of the second substrate, P i . The crystal structure of Bifidobacterium longum Xfp confirmed the reaction mechanism proposed by Yevenes and Frey (19). We suspect that C. neoformans Xfp2 follows the same reaction mechanism as the bacterial Xfps but with the added complexity of allosteric regulation that influences substrate binding affinity.…”
Section: Figsupporting
confidence: 80%
“…Therefore, the product E4P is formed by the interaction of TPP and F6P in the absence of the second substrate, P i . The crystal structure of Bifidobacterium longum Xfp confirmed the reaction mechanism proposed by Yevenes and Frey (19). We suspect that C. neoformans Xfp2 follows the same reaction mechanism as the bacterial Xfps but with the added complexity of allosteric regulation that influences substrate binding affinity.…”
Section: Figsupporting
confidence: 80%
“…We have recently shown that C. neoformans Xfp2 displays substrate cooperativity and is subject to allosteric regulation (6), neither of which has been reported for any of the bacterial Xfp enzymes (1,4,5,11), including the L. plantarum Xfp (2). To establish whether substrate cooperativity exists for L. plantarum Xfp, apparent kinetic parameters (Table 1) were determined in the acetyl phosphate-forming direction for the substrates F6P and P i by fitting experimental data to the Hill equation (equation 5), in which a Hill constant (h) greater than 1.0 represents positive cooperativity and a Hill constant less than 1.0 represents negative cooperativity (12,13).…”
Section: Resultsmentioning
confidence: 99%
“…The structure and mechanism of transketolase have been extensively studied, 121) but the three-dimensional structure and reaction mechanism of phosphoketolase has long been enigmatic, although phosphoketolase was discovered more than 50 years ago. [122][123][124] Very recently, crystallization of phosphoketolase from Lactococcus lactis 125) and structure determination of a substrate-free form of XFPK from B. longum JCM1217 126) were reported. Our group also succeeded in crystallization 127) and structure determination 128) of XFPK from B. breve (Fig.…”
Section: Bifid Shuntmentioning
confidence: 99%